From Neo-Corporatism to associative democracy: civil society's long and narrow path in the European Union - Zihnioğlu, Özge (Uluslararası İlişkiler Konseyi Derneği, Sogutozu Cad No 43, Tobb-Etu Bınası, Oda No 364, Sogutozu, Ankara 06560, Turkey, 2015)
The existence at the European level of civil society organizations (CSOs), acknowledged nowadays as indispensable actors of both the integration process and the enlargement strategy of the European Union, has a long history. This article examines the European Union's initiatives towards CSOs, which could now be accepted as a policy on its own, and the development of this relation in terms of neo-corporatism and associative democracy models. This article reveals the transformation of this policy from the one that initially had aspects of neo-corporatist model only and thus included a limited group of CSOs, to one that involves aspects of associative democracy comprising a larger group of CSOs, following European Social Dialogue, Civil Dialogue and the recent enlargement strategy of the Union.
Keywords: European Union; Civil Society; Neo-Corporatism; Associative Democracy